Anisotropic flow and flow fluctuations of identified hadrons in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Journal of high energy physics, 2023)
The first measurements of elliptic flow of π±, K±, , , , ϕ, , and using multiparticle cumulants in Pb-Pb collisions at = 5.02 TeV are presented.